ETHNIC AND ATOPIC DERMATITIS: WHAT HAVE WE LEARNED IN ASIAN POPULATION? - Prakoeswa, Cita (Indonesian Journal of Tropical and Infectious Disease, 2012)
Atopic Dermatitis (AD) is a chronic inflammatory skin disease, with relapsing remitting course. Management of AD is challenging due to the complexities of this disease. Two hypotheses concerning the mechanism of AD have been proposed. One holds that the primary defect resides in an immunologic disturbance that causes Ig E-mediated sensitization, with epithelial barrier dysfunction regarded as a consequence of the local inflammation. The others propose that an intrinsic defect in the epithelial cells leads to the barrierdysfunction; the immunologic aspects is considered to be an epiphenomenon. Many studies support that AD is a complex trait which has interactions between genes and environmental factors contributing to disease manifestation, but the result of replicate association between genetic markers and AD is inconsistence. An important factor contributing to this inconsistency is related to population diversity. It is possible that certain genetic markers might contribute to increase the risk in certain ethnic population but not in others, either because of the differences in frequencies of the risk alleles and the specific genes interaction. There is limited information about the role of ethnicity in Asian population. The overall purpose of this review is to present an update on ethnicity approach of AD in Asian population. Research on prevalence, risk factor, innate and adaptive immune response genes, skin barrier dysfunction genes and geneenvironmentinteraction such as epigenetic, is discussed. It is generally approved that the ethnicity of study subject is a key factor in interpreting genetic polymorphism studies. Therefore, discussion of some current areas of research about polymorphism are presented, including filaggrin (FLG) gene and CD14 C-159TSNP. Addressing the issues described above may improve our understanding of AD pathogenesis that has implications for the clinical management of AD.